1983
DOI: 10.1111/j.1365-2125.1983.tb02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of midazolam and oxazepam in insomniacs.

Abstract: In a multicentre, double‐blind, parallel study performed in 78 hospitalized patients who complained of mild, moderate or severe insomnia, the efficacy and safety of 15 mg midazolam were compared with those of 15 mg oxazepam, both orally administered. The results showed statistically significant better results in the onset of sleep in the patients treated with midazolam. Other sleep parameters, such as quality and duration of sleep as well as the condition of the patients on morning awakenings, were also improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The studies by Feldmeier and Kapp and Gallais et al reported a statistically significant reduction in sleep latency with midazolam (15 mg orally) compared to placebo (median difference of 30–53%, p<0.05); however, only Feldmeier and Kapp 34 found oxazepam (15 mg orally) to be superior to placebo (median difference 16%, p<0.05). Gallais et al 35 found midazolam 15 mg orally to be superior to oxazepam 50 mg orally ( table 3 ) as did Lupolover et al 36 (15 mg doses for midazolam and oxazepam), but only after 3 days of treatment ( table 3 ).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The studies by Feldmeier and Kapp and Gallais et al reported a statistically significant reduction in sleep latency with midazolam (15 mg orally) compared to placebo (median difference of 30–53%, p<0.05); however, only Feldmeier and Kapp 34 found oxazepam (15 mg orally) to be superior to placebo (median difference 16%, p<0.05). Gallais et al 35 found midazolam 15 mg orally to be superior to oxazepam 50 mg orally ( table 3 ) as did Lupolover et al 36 (15 mg doses for midazolam and oxazepam), but only after 3 days of treatment ( table 3 ).…”
Section: Resultsmentioning
confidence: 89%
“…Two randomised controlled trials, Feldmeier and Kapp 34 (n=50) and Gallais et al 35 (n=51), compared the effects of midazolam and oxazepam to placebo. One randomised controlled trial by Lupolover et al 36 (n=78) compared midazolam to oxazepam. Sleep latency was measured by third-party observation or patient questionnaire in all three studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations